ANALISIS KEMAMPUAN BERHITUNG PEMBELAJARAN MATEMATIKA PADA KURIKULUM MERDEKA KELAS II SDN 03 KERANGAN PURUN - Anggel Jendera; Septian Peterianus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the numeracy skills of second-grade students at SDN 03 Kerangan Purun in mathematics learning based on the Independent Curriculum. The research method used was qualitative with a descriptive approach and a case study design. The study subjects consisted of 13 second-grade students, including 8 boys and 5 girls. Data collection techniques were conducted through observations using a Likert scale, semi-structured interviews with teachers and students, and documentation. The results showed that the distribution of students' numeracy skills varied, with 61.5% of students falling into the "Good" category and 38.5% falling into the "Poor" category. Specific findings revealed that students generally possessed procedural understanding but were weak in deep conceptual understanding, such as an inability to explain the rationale for number values ​​or mathematical thinking processes. Although the implementation of the Independent Curriculum through project-based learning successfully increased the enthusiasm of students with strong foundations, challenges arose for students with lower basic skills who required intensive support (scaffolding). Overall, students' numeracy skills still need to be improved through more innovative and consistent learning strategies to strengthen their mathematical foundations.